1817. Benchmarking Outpatient Antimicrobial Use in Manitoba Through Population-Based Research. (26th November 2018) - Fanella, Sergio; Purewal, Rupeena; Dragan, Roxanna; Prior, Heather J; Stevenson, Dale; Valdivia, Jeff; Ruth, Chelsea
Abstract: Background: In Canada, there is limited knowledge about benchmarking and trends in provincial outpatient antimicrobial prescribing. We used de-identified population-level data (including all outpatient prescription dispensations) to describe and analyze temporal trends in antimicrobial prescribing and to determine what population level indicators best assess quality of antibiotic prescribing in outpatients. Methods: This population-based study used data from the Manitoba Population Research Data Repository, a comprehensive provincial collection of administrative, registry, and other data about residents of Manitoba, including health, education, and social services, all linked by a unique identifier. The first of three project objectives focused on examining prescription utilization trends for antimicrobials in the overall population by drug subclass as prescriptions/1, 000 individuals/day between 2011 and 2016. Crude and age- and sex-adjusted rates as well as relative rates were calculated using SAS V9.4. Results: The adjusted prescription rates by RHA relative to the RHA with the lowest rates (Southern RHA) in 2016 showed substantial variation across regions, with one region's rate 1.48 times greater than Southern RHA ( P < 0.0001). In 2016, there were 878, 416 antibiotic prescriptions overall in the province of Manitoba. Of these, 86.33% (758, 295) were from physicians, 9.42% (82, 778) were from dentists, 3.94% (34, 611) from nurse practitioners, 0.26% (2315) from pharmacists, and 0.01% (81) from midwives. In 2016, the proportion of outpatient visits that resulted in an antibiotic prescription by age group, were 18.2% (1–4 years old), 15.3% (5–9 years), 11.1% (10–14), 8.2% (15–64), 5.3% (65+ years). Conclusion: In Manitoba, there is substantial variability in the rate of antimicrobial prescribing across regions, despite adjustment for differing age and sex distribution. There is a considerable amount of antimicrobial prescribing by nonphysicians. Future phases of this deliverable will focus on patterns of service use of antimicrobials across Manitoba, including appropriateness. The goal would be to develop a province-wide framework for prescriber prescribing feedback reporting, to our knowledge, the first of its kind in Canada. Disclosures: All authors: No reported disclosures.